Preparation, Structure, and Reactivity of Pseudocyclic Benziodoxole Tosylates: New Hypervalent Iodine Oxidants and Electrophiles. Issue 3 (1st December 2016) - Yoshimura, Akira; Klasen, Scott C.; Shea, Michael T.; Nguyen, Khiem C.; Rohde, Gregory T.; Saito, Akio; Postnikov, Pavel S.; Yusubov, Mekhman S.; Nemykin, Victor N.; Zhdankin, Viktor V.
Abstract: New pseudocyclic benziodoxole tosylates were prepared by the treatment of 1‐hydroxybenziodoxolones with p ‐toluenesulfonic acid or via ligand transfer reaction between PhI(OH)OTs (Koser's reagent) and substituted 2‐iodobenzoic acids under mild condition. Single crystal X‐ray crystallography of these compounds revealed a pseudocyclic structure with a short intramolecular interaction of 2.362 Å between oxygen and iodine in the iodoxole ring. Pseudocyclic benziodoxole tosylates readily react with various organic substrates as electrophiles or oxidants to afford the corresponding iodonium salts or the products of oxidation. Furthermore, these compounds can be used as efficient recyclable hypervalent iodine reagents. The reduced form of a pseudocyclic benziodoxole tosylate, 2‐iodobenzoic acid, can be efficiently recovered from the reaction mixture by a simple acid–base liquid–liquid biphasic procedure. Abstract : Oxid‐I‐sing : Pseudocyclic benziodoxole tosylates readily react with various organic substrates as electrophiles or oxidants to afford the corresponding iodonium salts or the products of oxidation.